1980
DOI: 10.1007/bf00267209
|View full text |Cite
|
Sign up to set email alerts
|

Electron microscopic mapping and sequence analysis of the terminator for the early message of E. coli phage T7

Abstract: The terminator position of T7 early messenger RNA was determined by electron microscopic measurements. The end of the RNA was mapped at a position 18.9% from the left end of T7 DNA, and 145 +/- 25 nucleotides from the right end of the Hpa I fragment Q. The sequence of the Hpa I Q fragment was determined around this position, and a terminator-like structure was detected in position 193 to 169 from the right end of fragment Q.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
12
0

Year Published

1980
1980
1988
1988

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…Our data are in good agreement with these sequences (3-7~ higher for the triplet of segments 7, 8 and 9; 3"9~o lower for segment 11 of bovine rotavirus assuming its real number of bp to be very close to that of segment 11 of the human Wa strain). Priess et al (1980) found a linear relationship between length and number of bp of dsDNA in the range of 400 to 10000 bp and there is no reason that this should not be the case for the size range of dsRNAs investigated (Vasquez & Kleinschmidt, 1968). Our measurements agree, with a difference of ~< 6~ (Table 1, column 8), with the cDNA size estimates of size classes II (segments 5 and 6), III (segments 7 to 9) and IV (segments 10 and 11) (Both et al, 1982), whereas they are 8 to 17 ~ lower for molecules of size class I (segments 1 to 4).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Our data are in good agreement with these sequences (3-7~ higher for the triplet of segments 7, 8 and 9; 3"9~o lower for segment 11 of bovine rotavirus assuming its real number of bp to be very close to that of segment 11 of the human Wa strain). Priess et al (1980) found a linear relationship between length and number of bp of dsDNA in the range of 400 to 10000 bp and there is no reason that this should not be the case for the size range of dsRNAs investigated (Vasquez & Kleinschmidt, 1968). Our measurements agree, with a difference of ~< 6~ (Table 1, column 8), with the cDNA size estimates of size classes II (segments 5 and 6), III (segments 7 to 9) and IV (segments 10 and 11) (Both et al, 1982), whereas they are 8 to 17 ~ lower for molecules of size class I (segments 1 to 4).…”
mentioning
confidence: 99%
“…The sequence of the $2 gene of reovirus (Cashdollar et al, 1982) confirms the corresponding part of these data. From measurements of sequenced dsDNA standards by electron microscopy (Priess et al, 1980) a number of 1.91 × 106 mol. wt.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Purified inserts were then denatured and hybridized to 428 or 26S RNA in a buffer containing 80% (vol/vol) formamide (29). The nucleic acids were treated with gene 32 protein of the T4 phage and adsorbed to mica sheets (30). The length of the insert molecule and its location (that is, its distance from the 3' end of the RNA molecule) were measured.…”
mentioning
confidence: 99%
“…The tl terminator has recently been accurately mapped, by DNA and RNA sequence studies, at 18.97% from the left end of the DNA (2,15,16).…”
Section: Introductionmentioning
confidence: 99%